2017
DOI: 10.1016/j.str.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Cryoelectron Microscopy Maps of Human Papillomavirus 16 Reveal L2 Densities and Heparin Binding Site

Abstract: Human papillomavirus (HPV) is a significant health burden and leading cause of virus-induced cancers. The current commercial vaccines are genotype specific and provide little therapeutic benefit to patients with existing HPV infections. Host entry mechanisms represent an excellent target for alternative therapeutics, but HPV receptor use, the details of cell attachment, and host entry are inadequately understood. Here we present near-atomic resolution structures of the HPV16 capsid and HPV16 in complex with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
70
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 71 publications
12
70
1
1
Order By: Relevance
“…However, these have not been clearly mapped, and structural data are not yet available. Recent high-resolution reconstruction of cryoelectron microscopic images of HPV16 pseudovirions provided evidence for L2 density present on the outer capsid surface is suggestive of interaction between the L1 and L2 proteins (62). This supports previous findings based on the accessibility of L2 epitopes, which have suggested that L2 protein penetrates the capsid barrier allowing binding of L2 specific antibodies to N-terminal segments (residues 60 to 120) (4).…”
Section: Discussionsupporting
confidence: 82%
“…However, these have not been clearly mapped, and structural data are not yet available. Recent high-resolution reconstruction of cryoelectron microscopic images of HPV16 pseudovirions provided evidence for L2 density present on the outer capsid surface is suggestive of interaction between the L1 and L2 proteins (62). This supports previous findings based on the accessibility of L2 epitopes, which have suggested that L2 protein penetrates the capsid barrier allowing binding of L2 specific antibodies to N-terminal segments (residues 60 to 120) (4).…”
Section: Discussionsupporting
confidence: 82%
“…These molecular envelopes demonstrate that heparin asymmetrically decorates rather than symmetrically decorates the surface of the capsid, the latter of which has been demonstrated for a number of icosahedral viruses. This may be because prior structural studies of icosahedral viruses in complex with heparin utilized averaging techniques that may have eliminated the asymmetric distribution of heparin on the capsid surface (53,54,(57)(58)(59)(60). The packing of capsids into a crystal for X-ray crystallography inherently imposes the averaging of structures (61).…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the location of the insertion and whether the whole peptide is readily displayed on the surface of the VLP and to the immune system. Modelled cryo-electron microscopy images of MS2 [79] and HPV16 L1 [80] seem to show that the N-termini of MS2 coat proteins and the DE loops of HPV16 L1 coat proteins (where the peptides are inserted) are readily exposed on the surface of their icosahedral structures compared with the H4 helix of HPV16 L1 (Figure 4). In addition to this, insertions at these different locations can affect the assembly of the chimeric coat proteins into VLPs and ultimately, their immunogenicity.…”
Section: Expert Commentary and Perspectives For The Futurementioning
confidence: 99%